2010
DOI: 10.1175/2010jcli3402.1
|View full text |Cite
|
Sign up to set email alerts
|

An Enhancement of Low-Frequency Variability in the Kuroshio–Oyashio Extension in CCSM3 owing to Ocean Model Biases

Abstract: Enhanced decadal variability in sea surface temperature (SST) centered on the Kuroshio Extension (KE) has been found in the Community Climate System Model version 3 (CCSM3) as well as in other coupled climate models. This decadal peak has higher energy than is found in nature, almost twice as large in some cases. While previous analyses have concentrated on the mechanisms for such decadal variability in coupled models, an analysis of the causes of excessive SST response to changes in wind stress has been missi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
(52 reference statements)
4
11
0
Order By: Relevance
“…This overestimation of the simulated anomalies is consistent with the overestimation of the frontal gradient in the climatological-mean SST (purple contour; see also excursion of the SAFZ in the model that is in realistic magnitude (Fig. Thompson and Kwon 2010). In fact, both the SST anomalies and climatological-mean SST gradient in the model are nearly twice as large as their observational counterpart ( Fig.…”
Section: Validation Of the Cgcm Simulationsupporting
confidence: 80%
“…This overestimation of the simulated anomalies is consistent with the overestimation of the frontal gradient in the climatological-mean SST (purple contour; see also excursion of the SAFZ in the model that is in realistic magnitude (Fig. Thompson and Kwon 2010). In fact, both the SST anomalies and climatological-mean SST gradient in the model are nearly twice as large as their observational counterpart ( Fig.…”
Section: Validation Of the Cgcm Simulationsupporting
confidence: 80%
“…Like the traditional PDO index (PC-PDO), computed as the leading principal component of North Pacific SST anomalies (20-70 • N, Figure 1b), its warm (positive) phase is associated with cooling in the Kuroshio-Oyashio Extension (KOE) concurrent with warming along the west coast of North America. The LFC-PDO pattern is similar to the PDO-like anomaly pattern obtained from LFCA of observed Pacific SSTs over the twentieth century , with the biggest difference being the larger amplitude of KOE SST anomalies in the CMIP5 models, a known bias of low-resolution climate models (Thompson & Kwon, 2010). The warming associated with LFC-PDO is about half as strong as that associated with PC-PDO but extends farther west into the Bering Sea and Sea of Okhotsk.…”
Section: The Interdecadal Component Of the Pdosupporting
confidence: 72%
“…The steady state Sverdrup balance governing the oceanic response to wind stress forcing is well resolved, though nonlinear and eddy dynamics in the KOE are not, leading to mean state biases in the KOE system and stronger and larger-scale KOE SST variability in low-resolution models than in observations and high-resolution models (Thompson & Kwon, 2010). The steady state Sverdrup balance governing the oceanic response to wind stress forcing is well resolved, though nonlinear and eddy dynamics in the KOE are not, leading to mean state biases in the KOE system and stronger and larger-scale KOE SST variability in low-resolution models than in observations and high-resolution models (Thompson & Kwon, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…6b, which shows no overlap in the location of the KOE based on altimetry data (which captures the current) and the maximum in j=SSTj. Because our analysis examines the SST, we cannot comment directly on the ocean currents, but previous research has shown that coarse-resolution models like those used in this study produce a single, merged front that has both the strong ocean current and the SST front rather than having separate Kuroshio and Oyashio Extension fronts (e.g., Thompson and Kwon 2010). In the analysis presented here, the strong collocation of the T DIFF , j=SSTj, and s BI may be a result of the merged locations of the SST gradient and the ocean currents in the CMIP5 models, and for ERA-I it relates to the reduced spatial resolution we use for the analysis.…”
Section: B Analysis Methodsmentioning
confidence: 99%